Performance of a multiplex PCR pneumonia panel for the identification of respiratory pathogens and the main determinants of resistance from the lower respiratory tract specimens of adult patients in intensive care units - Lee, Sze Hwei; Ruan, Sheng-Yuan; Pan, Sung-Ching; Lee, Tai-Fen; Chien, Jung-Yien; Hsueh, Po-Ren (Journal of microbiology, immunology and infection, 2019)
Timely diagnostic investigation to establish the microbial etiology of pneumonia is essential to ensure the administration of effective antibiotic therapy to individual patients. We evaluated a multiplex PCR assay panel, the FilmArray® pneumonia panel (FilmArray PP, BioFire Diagnostics), for detection of 35 respiratory pathogens and resistance determinants and compared the performance of the standard-of-care test in intensive care unit patients with lower respiratory tract infections. Among the 59 endotracheal aspirates and bronchoalveolar lavage specimens obtained from 51 adult patients, FilmArray PP was effective in detecting respiratory bacterial pathogens with an overall positive percent agreement of 90% (95% confidence interval [CI], 73.5–97.9%) and negative percent agreement of 97.4% (95% CI, 96.0–98.4%). FilmArray PP semi-quantitative reporting demonstrated a concordance rate of 53.6% for the culture-positive specimens and 86.3% for the culture-negative specimens. FilmArray PP detected 16 viral targets, whereas the conventional viral isolation failed, except influenza A, which showed 100% concordance with PCR. Coinfections were detected in 42.3% of the specimens. Substantial discrepancies were observed in identifying antimicrobial resistance gene targets and in the susceptibility testing. However, FilmArray PP may still be useful at the early stage of pneumonia before culture and susceptibility test reports are available. Consequently, the results of FilmArray PP might alter the antibiotic prescription in 40.7% of the patients. FilmArray PP offers a rapid and sensitive diagnostic method for lower respiratory tract infections. However, clinical correlation is advised to determine its significance in interpreting multiple pathogens and detection of genes involved in antimicrobial resistance.